ESTIMATING COMPETITIVENESS OF ADVERTISING COMPANY THROUGH INTEGRAL INDEXES - Аleksej V. Katernyuk; Elizaveta V. Mezhevaya (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article studies a well-known integral methodology of estimating company competitiveness. It shows the possibility to use it in practice, in particular for advertising agencies. In order to estimate competitiveness such methods as formalization, comparison, modeling and sociometry were used. The author came to the conclusion about possible application of this methodology for advertising service assessment. Models used earlier for estimation of competitiveness were oriented to the product as a physical object with a number of characteristic s (from compliance with standards to subjective appraisal by customers). Assessment of service competitiveness includes both the attitude to the product (in case service rendering is connected with a physical product) and the attitude to the company that provides the service, which can be positive, if the process of sale/purchase was pleasant or adverse, if not. The author put forward an extended appraisal of features of the whole process of client servicing. In view of its practical application this algorithm can be used both by advertising agencies (market participants) and state bodies controlling competition of the market (such as the Federal Antitrust Service).